2007
DOI: 10.1182/blood-2006-04-016378
|View full text |Cite
|
Sign up to set email alerts
|

Duplicate VegfA genes and orthologues of the KDR receptor tyrosine kinase family mediate vascular development in the zebrafish

Abstract: Vascular endothelial growth factor A (VEGFA) and the type III receptor tyrosine kinase receptors (RTKs) are both required for the differentiation of endothelial cells (vasculogenesis) and for the sprouting of new capillaries (angiogenesis). We have isolated a duplicated zebrafish VegfA locus, termed VegfAb, and a duplicate RTK locus with homology to KDR/FLK1 (named Kdrb). Morpholinodisrupted VegfAb embryos develop a normal circulatory system until approximately 2 to 3 days after fertilization (dpf), when defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 60 publications
6
126
1
Order By: Relevance
“…46) Furthermore, a recent study reported the cloning and characterization of duplicated zebrafish genes kdra and kdrb, and they found that morpholinos targeting both forms resulted in defects in vasculogenesis. 65) The gene tested in this study is kdra. Is the other form kdrb involved in EXD inhibition of vessel formation in zebrafish embryos?…”
Section: Discussionmentioning
confidence: 99%
“…46) Furthermore, a recent study reported the cloning and characterization of duplicated zebrafish genes kdra and kdrb, and they found that morpholinos targeting both forms resulted in defects in vasculogenesis. 65) The gene tested in this study is kdra. Is the other form kdrb involved in EXD inhibition of vessel formation in zebrafish embryos?…”
Section: Discussionmentioning
confidence: 99%
“…How these expression patterns were established and maintained is the subject of much debate since the benefit to the organism of having two biologically distinct but functionally related genes is not always apparent (Force et al, 1999). Many examples of this phenomenon have been described including the following zebrafish coorthologues, hoxB1a and b (McClintock et al, 2002), sonic hedgehog (shh) and tiggywinkle hedgehog (twhh) (Hammond et al, 2003), protocadherin15 (pcdh15a and pcdh15b) (Seiler et al, 2005), VEGFAa and VEGFAb (Bahary et al, 2007), and progranulin A and B (Cadieux et al, 2005). In the present study, we have cloned two zebrafish cDNA sequences designated PC5.1 and PC5.2.…”
Section: Characterization Of Zebrafish Pcsk5 Co-orthologuesmentioning
confidence: 99%
“…Like all vertebrates, with the exception of placental mammals, zebrafish have four Vegf receptors (Flt1, Kdr, Kdr-like and Flt4); Kdr-like (also known as Kdrl) was lost during the evolution of placental mammals (Bussmann et al, 2007;Bussmann et al, 2008). Although Kdr and Kdr-like represent separate classes of Vegf receptor, the duplicated VEGFA orthologs Vegfaa and Vegfab can bind to, and activate, both receptors in vitro (Bahary et al, 2007 …”
mentioning
confidence: 99%
“…1A) showing the conservation of VEGF ligands in zebrafish. The duplicated zebrafish VEGFA orthologs vegfaa and vegfab (Bahary et al, 2007), as well as zebrafish vegfc (Ober et al, 2004) and vegfd (Song et al, 2007), have all been described previously. From our analyses, we identified zebrafish vegfb, which is syntenic to human VEGFB (not shown) and with orthologs that are present in other fish species.…”
mentioning
confidence: 99%